Synthesis and Antifeedant Activity of Racemic and Optically Active Hydroxy Lactones with the p-Menthane System - Grudniewska, Aleksandra; Kłobucki, Marek; Dancewicz, Katarzyna; Szczepanik, Maryla; Gabryś, Beata; Wawrzeńczyk, Czesław (PLOS ONE, 2015)
Two racemic and two enantiomeric pairs of new δ-hydroxy-γ-lactones based on the p-menthane system were prepared from racemic and optically active cis- and trans-piperitols. The Johnson-Claisen rearrangement of the piperitols, epoxidation of the γδ-unsaturated esters, and acidic lactonization of the epoxy esters were described. The structures of the compounds were confirmed spectroscopically. The antifeedant activities of the hydroxy lactones and racemic piperitone were evaluated against three insect pests: lesser mealworm, Alphitobius diaperinus (Panzer); Colorado potato beetle, Leptinotarsa decemlineata (Say); and peach-potato aphid, Myzus persicae (Sulz.). The chemical transformation of piperitone by the introduction of a lactone moiety and a hydroxy group changed its antifeedant properties. Behavioral bioassays showed that the feeding deterrent activity depended on the insect species and the structure of the compounds. All hydroxy lactones deterred the settling of M. persicae. Among chewing insects, the highest sensitivity showed A. diaperinus adults.